Voltage and active power management control of pv source distributed generations under unbalanced voltage of non-islanded microgrid - Wan Azman, Wan Abdullah; Abu Zaharin, Ahmad (Institute of Physics, 2022)
Key solution for future electrical power generation depends on alternative energy such as Solar Energy and renewable energy. Solar energy can be harvested by using a fast growing technique like Photovoltaic Plants (PV) in order to fulfill the demand of electrical energy. Proportional Integral Derivative Controller (PID controller) is added together with power electronic components such as boost converter combined with suitable controller of different maximum power point tracking techniques (MPPT) combined to optimized the PV system. In this paper, sudden irradiance and cell temperature variations are the variable input tested on grid PV systems modeled in MATLAB SIMULINK software. Incremental Conductance PID Controller with the trial and error method is used randomly in order to have good and efficient of transmission of energy and avoiding the unbalance voltage at the same time enhancing the protection system from bad disturbances. The stability of the system is checked to counter various irradiance and temperature in order to have a balance voltage and optimum energy. The new controller then been compared with previous literature in order to ensure the designed controller operating following the state of boundary and limitation of the operation.